AN ANALYSIS OF THE USE OF BRITISH ENGLISH AND AMERICAN ENGLISH TOWARD SPEAKING ABILITY IN THE STUDENTS’ TELEGRAM ACCOUNTS OF STKIP PGRI UNIVERSITY OF SIDOARJO - Putri Giyarti Mailina Giyarti; Siti Aisyah (STKIP PGRI SIDOARJO, 2022)
This research examines the use of British and American English in speaking skills on STKIP PGRI Sidoarjo University student accounts. The goal of this study was to examine the vocabulary of British English and American English on the Telegram accounts of STKIP PGRI Sidoarjo University students. This study employs a qualitative approach with descriptive analysis techniques. Purposive sampling from group voice calls used to practice speaking English was used for the sampling technique. The Telegram accounts examined are those of STKIP PGRI Sidoarjo University students. The accounts examined were five STKIP PGRI Sidoarjo student accounts. According to the findings of this study, the researcher examined the differences between British and American English speech accents on students' Telegram. Second, the researcher examines the skills of speaking about grammatical suitability, accent conversation, and sentence context. Keywords: British dan American English; speaking; telegram voice call group